Knowledge management and innovation in network organizations emerging research and opportunities - Kisielnicki, Jerzy (Advances in business information systems and analytics (ABISA) book series., 2019)
"This book addresses the phenomenon and concept of a network organization. It presents the concept of innovation and the evolution of this term in the sciences of organization and management. It also addresses selected problems concerning the design and functioning of the decision-making system in traditional and network organizations"--